A Theory and Implementation Evaluation of The Allan Gray Entrepreneurial Challenge - Dumutu, Ismail Ombo Michael (Accounting and Accountability in Africa, 2025)
Youth unemployment remains a pressing concern in South Africa, with an alarming unemployment rate of 44.7% recorded among individuals aged 15 to 34 in the fourth quarter of 2021. This calls for urgent intervention due to the associated ramifications of poverty, social exclusion, inequality, crime, and social instability. Despite a positive attitude towards entrepreneurship, South Africa lags in entrepreneurial activity compared to other developing countries. Recognizing the pivotal role of entrepreneurial education, the Allan Gray Orbis Foundation (AGOF) launched the Allan Gray Entrepreneurship Challenge (AGEC) in 2017. This online simulation ‘game' seeks to develop entrepreneurial competencies in primary, secondary, and Technical and Vocational Education and Training (TVET) college students in an interactive manner. Following an internal review, the programme was adapted in 2022 to enhance the gaming and learning experience of beneficiaries. This evaluation aimed to surface and assess the plausibility of the theory of change underlying the adapted AGEC and assess the extent to which the game's design and implementation were adapted in line with the proposed recommendations. To elicit the programme theory, the following questions were employed: • What is the underlying logic and theory of AGEC? • To what extent is the AGEC programme theory and logic plausible? • What aspects of the AGEC programme can be altered to optimize the desired outcomes? The following questions were used to assess implementation effectiveness: • To what extent are the proposed changes to the AGEC game being implemented as planned? • What are the potential barriers to successful implementation? • Which, if any, improvements to the delivery of the AGEC game are recommended by participants? Combining exploratory and descriptive research designs, the evaluator collected data through workshops, document reviews, and key informant interviews with seven champion teachers and seven students. The following key findings were identified (i) the AGEC theory and underlying causal assumptions were plausible; (ii) while the extended gameplay period aligned with successful programmes, challenges arose in maintaining student focus; (iii) the original leaderboard with weekly prizes was found to be more motivating for students; (iv) technical issues hampered the user experience, leading to decreased interest and high dropout rates among students; (v) shifting from teacher-assessed weekly assignments to automated Built-in Assessment impacted debrief sessions negatively with fewer sessions being organized; (vi) insufficient organizational support was offered to teachers and students; and (vii) resource shortages, exacerbated by the COVID-19 pandemic, posed challenges, particularly in rural schools. Key recommendations include ensuring adherence to planned debrief sessions and peer-to-peer learning to sustain engagement, reintroducing weekly prizes alongside end-of-module quizzes to maintain motivation and engagement, improving teacher training and support to improve programme delivery, providing resources such as devices (computers, tablets, etc.) and internet connectivity to low-income schools, rigorous testing of the AGEC game before launch, and adding a live chat feature to strengthen technical support. This is meant to improve the overall learning experience for students, increasing the likelihood of attaining desired outcomes.